Exoskeleton Walk Training in Paralyzed Individuals Benefits From Transcutaneous Lumbar Cord Tonic Electrical Stimulation - Shapkova, Elena Y.; Pismennaya, Elena V.; Emelyannikov, Dmitriy V.; Ivanenko, Yury (Frontiers in Neuroscience, 2020)
In recent years, advanced technologies featuring wearable powered exoskeletons and neuromodulation of lumbosacral spinal networks have been developed to facilitate stepping and promote motor recovery in humans with paralysis. Here we studied a combined effect of spinal cord electrical stimulation (SCES) and exoskeleton walk training (EWT) during an intensive 2-week rehabilitative protocol in spinal cord injury individuals (n=19, American Spinal Injury Association Impairment Scale (AIS) A-11, B-5, C-3). The purpose of this study was to evaluate the compatibility of methods and to explore the main effects of combined SCES and EWT. All participants had a chronic state of paralysis (1-11 yrs after trauma). In addition, in the control group (n=16, AIS A-7, B-5, C-4), we performed EWT without SCES. For EWT, we used a powered exoskeleton (ExoAtlet), while stability was assisted by crutches, with automatic arrest of stepping if excessive torques were detected. SCES was applied to the level of the mid-lumbar cord over the Th12 vertebra at 1 or 3 pulses/s (4 individuals with severe spasticity were also stimulated in an anti-spastic mode 67 pulses/s). The vertical component of the ground reaction force was recorded using the F-Scan system at the onset and after training with SCES. EWT with SCES significantly increased the foot loading forces, could decrease their asymmetry and 8 out of 19 subjects improved their Hauser Ambulation Index. The anti-spastic mode of stimulation also allowed individuals with severe spasticity to walk with the aid of the exoskeleton. Participants reported facilitation when walking with SCES, paresthesia in leg muscles and new non-differential sensation of passive motion in leg joints. Neurological examination showed an increase of tactile (7) and/or pain (7) sensation and an increase of the AIS motor scale in 9 individuals, including both incomplete and complete paralysis. Improvements in the neurological scores were however limited in the control group (EWT without SCES). The results suggest that SCES may facilitate training and walking in the exoskeleton by activating the locomotor networks and augmenting compensative sensitivity.